Design of optoacoustic imaging system for deep penetration medical diagnostics - Tan, Angus Xuan (2018)
The Photoacoustic effect has garnered large and widespread interests in recent years, especially in the field of biomedical systems and technology. Owing to its enhanced performance capabilities in contrast conventional optical or ultrasound imaging, photoacoustic (PA) imaging is a hybrid imaging modality that employs the use of the PA effect to obtain the desired result. It combines the ideal range and resolution property of optical and ultrasound imaging respectively, and the extent of its capabilities are still under deep research. A particular area of biomedical interest in recent years was using the photoacoustic effect to measure blood flow.